KHAZANAH LEKSIKON KELAUTAN DALAM BAHASA MELAYU DIALEK SUKADANA - Mira Yunika Sari; Ahmad Rabi’ul Muzammil; Agus Syahrani (Universitas Tanjungpura, 2019)
AbstractThis study focused on marine lexicons in Malay language Sukadana. The research problem was how the form of the lingual unit of marine lexicon, the meaning of the marine lexicon, retains the Sukadana Malay language lexicon on adolescent, adult, and old speakers, as well as the RPP Indonesian alternative model with material on marine class VII Semester I according to the 2013 curriculum. Based on the analysis found 81 data of marine lexicons in Malay language Sukadana which are divided into two research groups, namely the activity of capturing marine products including lexicons of transportation equipment, there are 3 lexicon data, there are 15 lexicon data, there are 37 lexicon data, and part use techniques Fishing gear has 12 lexicon data, while marine processing activities include the name of food processing, there are 4 lexicon data, the name of material processing is 9 lexicon data, and the name of production processing is 1 lexicon data. Understanding of marine lexicons in Sukadana Malay language for adolescents 15-20 years old, adults 21-45, and aged ≥ 46 years for 81 lexicons from the results of research on understanding the lexicon of marine language in Sukadana Malay still persists among those ages. Keywords: Embedding Lexicon,Marine Lexicon, Meaning of Language Supplement Text Indonesia